EDUKASI DAN IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DALAM MENINGKATKAN KESADARAN SISWA DI SDN SUMBERBENDO II - Sinta Ma’sumah; Lailatun Ni’mah; Salzabiilah; Kholilurrohman Arif; Khoiriyah (DEVELOPMENT: Journal of Community Engagement, 2026)
This community service research aimed to increase students' awareness of Clean and Healthy Living Behaviors (PHBS) through education and hands-on practice. The method used was a participatory approach, with students providing interactive counseling and demonstrating clean living practices, including proper handwashing, personal hygiene, and school environmental management. Observations of the implementation of these practices revealed positive behavioral changes in students, including practicing handwashing before and after activities, disposing of trash properly, and maintaining classroom cleanliness. This activity increased individual awareness while strengthening a sustainable healthy school culture. These findings are expected to serve as a model for implementing the PHBS program in other elementary schools and provide practical contributions to community health promotion and prevention efforts